Pengukuran Output Ekonomi: Perspektif Islam Dan Konvensional Dalam Menilai Kesejahteraan Sosial - Darma, Satria (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Measuring economic output is an important aspect in economic analysis, and so far Gross Domestic Product (GDP) has been the main focus. However, criticism of GDP's limitations has prompted the development of alternative approaches, including the Human Development Index (HDI) and the World Happiness Index. In addition, Islamic economics offers a unique perspective by emphasizing the balance between material growth and spiritual well-being, as well as taking into account aspects such as distributional justice and sustainability. This article discusses various approaches to measuring economic output and welfare, and compares Islamic and conventional perspectives. Integration between conventional measurement methods and Islamic economic principles can provide new insights in measuring and understanding welfare in society, with the potential to improve welfare in a holistic and inclusive manner.